Integrating Management Fundamentals, Business Communication, and Negotiation Skills to Foster Collaborative Business Competencies - Jamilah Salahuddin; Eka Rakhmat Kabul (Greenation International Journal of Tourism and Management, 2026)
The increasing complexity of today’s business environment requires graduates to possess not only strong management knowledge but also effective communication, negotiation, and collaboration skills. In business and retail management education, these competencies are critical for preparing students to engage in real-world organizational and inter-organizational interactions. This study aims to examine how the integration of management fundamentals, business communication, and negotiation skills contributes to the development of collaborative business competencies among students. Using a quantitative approach, this study collected data from students enrolled in business and retail management programs at a vocational higher education institution. Data were gathered through structured questionnaires measuring perceptions of management fundamentals, business communication skills, negotiation skills, and collaborative business competencies. The data were analyzed using Structural Equation Modeling (SEM) to examine the direct and indirect relationships among the constructs. The results indicate that management fundamentals have a significant positive effect on both business communication and negotiation skills. Furthermore, business communication and negotiation skills were found to significantly enhance collaborative business competencies. The findings also reveal that business communication and negotiation skills partially mediate the relationship between management fundamentals and collaborative business competencies. These results suggest that management knowledge alone is insufficient to foster effective collaboration unless it is complemented by strong communication and negotiation capabilities. This study contributes to the literature by providing empirical evidence on the importance of an integrated learning approach in business and management education, particularly within vocational contexts. From a practical perspective, the findings highlight the need for curriculum designs that intentionally integrate management theory with applied communication and negotiation training to better prepare graduates for collaborative business environments.